2021
DOI: 10.1159/000518503
|View full text |Cite
|
Sign up to set email alerts
|

A Forgotten Ureteral Stent: Potential Risks for the Urinary Function

Abstract: A 32-year-old man presented with painless macrohaematuria. An endoscopic stone removal of the upper moiety of a left double kidney with ureter duplex was performed 4 years ago. The inserted ureteral catheter (DJ) was not removed although it was communicated to the patient and written in the discharge report. The DJ led to a large bladder stone, a total incrustation of the DJ, and a staghorn calculus of the upper moiety. Furthermore, renal function scintigraphy showed no clinically significant function of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Technological advances in stent design, constitutive materials and surface coating allow patients to tolerate stents more easily, and this may cause a decrease in patient compliance for stent removal [ 5 ]. Studies have found that stents were forgotten in up to 0.9–12.0% of patients [ 6 ]. Ureteral stents as foreign bodies should be removed or replaced after they have served their purposes before the intended maximal stent life (MSL).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in stent design, constitutive materials and surface coating allow patients to tolerate stents more easily, and this may cause a decrease in patient compliance for stent removal [ 5 ]. Studies have found that stents were forgotten in up to 0.9–12.0% of patients [ 6 ]. Ureteral stents as foreign bodies should be removed or replaced after they have served their purposes before the intended maximal stent life (MSL).…”
Section: Introductionmentioning
confidence: 99%